Investigating the effect of 8 weeks of aerobic training and Borage extract on the serum concentration of liver enzymes and lipid profile in rats with non-alcoholic fatty liver disease (NAFLD) - Bakhshizadeh, Atena; Abednatanzi, Hossein; Gholami, Mandana; Ghazalian, Farshad (Researcher Bulletin of Medical Sciences, 2025)
Objective: Non-alcoholic fatty liver disease is known as one of the chronic liver diseases that is closely related to obesity and metabolic disorders, and borage improves oxidative indices due to its antioxidant properties. The aim of this study is to investigate the effect of a part of aerobic exercise with borage extract on the serum concentration of liver enzymes and lipid profile in rats with non-alcoholic fatty liver disease. Materials and Methods: In this experimental study, 40 male Wistar rats weighing 250-300 grams were divided into 4 groups (N: 10). The groups were: Control group (suffering from fatty liver and receiving enough water and food/without exercise and supplements) supplement group (suffering from fatty liver and receiving 200 mg/kg borage extract) exercise group (suffering from fatty liver and doing aerobic exercise daily for 8 weeks) exercise + supplement group (suffering from fatty liver and receiving 200 mg/kg borage supplement and performing aerobic exercise for 8 weeks). At the end, blood was drawn from all the animals, then the serum lipid profile, including total cholesterol and triglycerides, as well as liver enzymes such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were measured by ELISA method. They were analyzed with SPSS and a significance level of <0.05. Results: The findings of the present study showed that in the comparison of total cholesterol serum level changes during the study period after poisoning, there was a significant decrease in the control groups (P=0.004) and supplement (borage extract) + exercise (0.047). P=0) was observed. Nevertheless, the training and supplementation groups showed a significant increase in serum total cholesterol levels during the study period. In addition, comparing the changes in serum triglyceride levels during the study period after poisoning, only a significant decrease was observed in the supplemented group (P=0.002). Also, comparing the changes of serum ALT level during the study period after poisoning, a significant increase in serum ALT level was observed in the control (P=0.045) and exercise (P=0.002) groups. The supplement group also showed a significant decrease in ALT serum level (P<0.001). In comparing the changes of AST serum level during the study period after poisoning, a significant decrease was observed in the control (P=0.003) and supplement (P=0.006) groups. Conclusion: The findings of the present study showed that 8 weeks of supplementing with borage extract alone reduced serum triglyceride, AST, and ALT levels, and 8 weeks of aerobic exercise with borage extract reduced total cholesterol levels in rats with non-alcoholic fatty liver disease.